Diseminasi Pengolahan Dodol Ketan Hitam Berbasis Smart Production Pada Kelompok Tani Maddaung - Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Syarif Nur; Andi Nurannisa; Andi Hasryningsih Asfar; Ady Kurnia (Jurnal Pengabdian UNDIKMA, 2022)
This community service activity aims to disseminate and train smart production-based black sticky rice dodol processing at the Maddaung Farmer Group, Latellang Village, so that partners can be more productive with the technology approach. The method of implementing this service is carried out in three stages, namely counseling, training, and mentoring. The evaluation instrument for this activity is a questionnaire via google form and analyzed descriptively. The result of this service indicates that there is an increase in the knowledge and skills of partners in processing black glutinous rice into smart production-based dodol by 90% and 94%, which indicates that this service activity directly affects the productivity of partners. The positive impact of the implementation of this service is that it can build the spirit of entrepreneurship, and make lunkhead a potential product as a superior product of the village with high commercial value characterized by Latellang Village.